Die Lehmhüttensiedlungen der Stadt Bagdad: Ein Beitrag zur Sozialgeographie orientalischer Städte - Wirth, Eugen (ERDKUNDE, 1954)
The author shows that the so-called slums of Bagdhad form not only physiognomically but also functionally an essential part of the town. They are, however, not slums in a European sense but rural settlements which have migrated to the town. The inhabitants of these slums are fellaheen who can thus continue to live in their accustomed village environment while also enjoying the advantages of life near a town, such as chances of employment and additional income, without having to meet the usually higher costs of accommodation and sustenance. This is the basis of further social advance in which many of these slum inhabitants succeed. These mud-hut quarters are on the other hand important as the location of Baghdad's milk supply. The milk there is not produced in the rural umland then delivered to the town, but the milk-producing livestock are kept in the town and the fodder is brought from outside. This change of location is quite advantageous from an economic point of view considering how rapidly milk turns sour during the summer months.